Initiating Equal Distribution of Inheritance: An Innovation in Islamic Inheritance Law in the Modern Era - Efendi, Zulfan; Siregar, Nurma Harana Mora (El-Sirry: Jurnal Hukum Islam dan Sosial, 2025)
This article explores the concept of equal distribution of inheritance within Islamic inheritance law in the contemporary context, presenting it as a remedy for the injustices frequently faced by women and as a way to resolve disputes that often occur among heirs due to differing views on asset distribution. The research background highlights traditional rules that grant larger shares to men, along with the associated social and economic consequences. The study utilizes a library research method with a qualitative approach, examining relevant literature to grasp the idea of equal inheritance distribution. The findings suggest that equal inheritance distribution can foster gender equality and improve women's status in society. This method is anticipated to mitigate family disputes and foster a more harmonious atmosphere. Nevertheless, obstacles such as cultural traditions and insufficient public awareness of Islamic inheritance law persist in hindering its application. The article underscores the significance of dialogue and consensus among heirs to achieve an equitable distribution that adheres to Sharia principles, ultimately contributing to a more just and prosperous society.